2022
DOI: 10.1126/sciadv.abm6155
|View full text |Cite
|
Sign up to set email alerts
|

An isogenic panel of App knock-in mouse models: Profiling β-secretase inhibition and endosomal abnormalities

Abstract: We previously developed single App knock-in mouse models of Alzheimer’s disease (AD) that harbor the Swedish and Beyreuther/Iberian mutations with or without the Arctic mutation ( App NL-G-F and App NL-F mice). We have now generated App knock-in mice devoid of the Swedish mutations ( App G-F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In addition, MS1262 has greater potency than any existing G9a inhibitors (e.g., BIX-01294, UNC0638, UNC0642). We studied the MS1262 effects on two AD mouse models, the 5XFAD and the APP NLGF knock-in (KI) 26 mice, which are clinically relevant mouse models of AD that comprehensively recapitulate major pathological features of AD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MS1262 has greater potency than any existing G9a inhibitors (e.g., BIX-01294, UNC0638, UNC0642). We studied the MS1262 effects on two AD mouse models, the 5XFAD and the APP NLGF knock-in (KI) 26 mice, which are clinically relevant mouse models of AD that comprehensively recapitulate major pathological features of AD patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MS1262 has greater potency than any existing G9a inhibitors (e.g., BIX-01294, UNC0638, UNC0642). We studied the MS1262 effects on two AD mouse models, the 5XFAD and the APP NLGF knock-in (KI) 26 mice, which are clinically relevant mouse models of AD that comprehensively recapitulate major pathological features of AD patients. Consistently, we found that intermittent MS1262 treatment of both types of AD mice not only fully restored cognitive functions to healthy levels but also reduced anxiety- and depressive-like behavior, typical noncognitive (affective) symptoms of AD patients.…”
Section: Introductionmentioning
confidence: 99%
“…We first assessed endogenous IgG accumulation in the brain parenchyma of an App-KI mouse line, App NL-G-F mouse model 30 . App NL-G-F line, which expresses humanized Aβ peptide and harbors the Swedish (KM670/671NL), Beyreuther/Iberian (I716F), and Arctic (E693G) mutations, manifests Aβ plaque deposition and cognitive impairments earlier than other App-KI mouse lines [30][31][32] . We used the mouse model aged 6 to 7 months to examine the accumulation of endogenous IgG in its brain parenchyma when memory impairment is observed 30 .…”
Section: Endogenous Igg Accumulation Associated With Aß Plaques In Ad...mentioning
confidence: 99%
“…At 8 months of age, Aβ plaques were detected in multiple brain regions with highest burden in cortical and hippocampal regions [ 99 ]. Initial Aβ deposition was observed as early as 4 months of age in APP GF mice and at 12 months of age, Aβ deposition in APP GF mice was detected to be in a much larger brain area than that in APP NL−F mice but in a lesser area than that in APP NLGF mice [ 100 ]. It was also found that p-tau 217, p-tau 231, and a fraction of p-tau 181 were detected around Aβ plaques only in APP NLGF mice but not in APP NL or wildtype mice, suggesting that these tau pathologies may be induced by Aβ plaque burden [ 101 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite an early and aggressive Aβ amyloidosis in APP NLGF , neuroinflammatory responses were not intense at 6–9 months of age, but greater reactive gliosis was observed in cortical and hippocampal regions by 15–18 months of age [ 98 ]. On the other hand, amyloidosis in APP GF mice were accompanied with neuroinflammation, as shown by reactive astrocytes and activated microglia at 22 months of age [ 100 ].…”
Section: Introductionmentioning
confidence: 99%